DAMPAK TRANSFORMASI DIGITAL TERHADAP EFEKTIVITAS LAYANAN ADMINISTRASI PUBLIK di DAERAH 3T - Olii, Rara Ayudyah; Tue, Noviyanti; Bakari, Sunarti; Pakaji, Lisnawati (Universitas Bina Taruna Gorontalo, 2025)
This study examines the impact of the implementation of digital transformation on public administration services in Garapia Village, North Gorontalo Regency, which is included in the category of Frontier, Remote, and Disadvantaged (3T) areas. Digital transformation is implemented through an online document registration system and a mobile application for health services. This study aims to evaluate the effectiveness, challenges, and impact of digitalisation on public services in this village. The qualitative research method used in examining the effects of digital transformation on the efficacy of public administration services in the 3T Region of North Gorontalo Regency involves an in-depth approach to understanding the phenomenon as a whole. This research combines various qualitative data collection techniques, while the object of this research to be interviewed in-depth is stakeholders at the village level, such as village heads, village government heads, community members, and community leaders. The study results show significant challenges in implementing digital transformation, including limited internet access, low digital literacy among the community, and lack of training and technical support for village government employees. Limited technological infrastructure hinders people's ability to access digital services optimally, while low levels of digital literacy slow down technology adoption. Efforts made by village governments, such as digital literacy training and collaboration with internet service providers, have shown positive results but still do not fully overcome all challenges.